2020
DOI: 10.31539/leea.v4i1.1728
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Students’ Motivation in Studying English During Covid-19 Pandemic

Abstract: This study focuses to investigate students’ motivation in studying English during Covid-19 Pandemic, whether they had intrinsic or extrinsic motivation. This research was a survey method and the technique sampling used in this study was random sampling. Furthermore, the instrument used questionnaire to collect the data. The questionnaire consists of 20 questions in which question 1-10 are questions for intrinsic motivation. The question 11-20 are extrinsic motivation. The result of this study shows that the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 6 publications
1
20
0
2
Order By: Relevance
“…Meanwhile, Subakthiasih and Putri's (2020) students demonstrated higher intrinsic motivation than extrinsic motivation learning English during the pandemic. They reported possessing self-driven nature to learn English as they wanted to improve their English skills.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Meanwhile, Subakthiasih and Putri's (2020) students demonstrated higher intrinsic motivation than extrinsic motivation learning English during the pandemic. They reported possessing self-driven nature to learn English as they wanted to improve their English skills.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, researchers (Fansury et al, 2020;Kaharuddin, 2020;Subakthiasih & Putri, 2020) have increased interest in investigating digital learning platforms for English learning during the pandemic. Integrating technology into the language class affected the motivation among English as a Foreign (EFL) learners in Kaharuddin's (2020) study directly and directly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, Wahyudin et al (2020) [5] research indicates a significant amount of student learning motivation in the high grade, with markers of having a positive outlook despite the pandemic condition. In the following research, Subakthiasih & Putri (2020) [6] explains that students had more inherent motivation than extrinsic desire to learn English. It shows that the student's motivation was more significant than the outside motivation of students.…”
Section: Introductionmentioning
confidence: 95%
“…Even though there are many technological facilities that can be used as alternative media during this pandemic, students' motivation to learn mathematics has actually decreased. Several previous studies have shown that student motivation decreases during the online learning process (Gustiani, 2020;Muslimin & Harintama, 2020;Subakthiasih & Putri, 2020). The decrease in motivation is caused by several factors, including bad internet network connection, improper media selection, and less conducive learning conditions.…”
Section: Introductionmentioning
confidence: 96%